Kesan Faktor Terminologi, Semantik dan 'Urf dalam Penghuraian Berkaitan Isu Makanan - Abdul Razak, Zainur Rijal; Wan Ahmad, Wan Azura; Abdul Rahman, Lubna; Abu Bakar, Arnida (Jurnal Fiqh, 2014)
The process of Quran interpretation actually requires a combination of knowledge of various disciplines. It is undeniable that the Arabic language factor is the branch of knowledge that must be considered when interpreting the Quranic verses. This is because the purpose of a particular interpretation of the Quran as a source of law should be construed in accordance with the views of Islamic scholars when influenced by language factors. The objective of this paper is to identify to what extent three factors, namely, Arabic terminology, semantics and 'urf, can affect the Quranic interpretation and hukum production of halal food issue. To achieve the objective, the library research method was used to analyse related verses in surah al-Ma'idah and al-An'am. The study found that there is a close relationship between terminology, semantics and 'urf with the interpretation and views of Muslim scholars on the issue of food in the Quran.